Благодійні податки на доходи: зарубіжний досвід - Тучак, Тетяна Володимирівна; Тучак, Тетяна (Економічний вісник, 2019)
У статті розглянуті сучасні та історичні форми благодійних (солідарних) податків. Благодійні податки можуть існувати у формі надбавок солідарності до податків на доходи або прибуток, надбавки до ціни певних категорій товарів, самостійних податків на майно, багатство, податку на непередбачуваний прибуток, податкового кредиту. Особливу увагу приділено меті запровадження та призначенню цих податків. Розглянуто досвід провідних зарубіжних держав щодо функціонування та модифікацій податків солідарності. Окреслено перспективи запровадження солідарних форм оподаткування на теренах Євросоюзу.

Introduction. Taxes in a socially oriented market economy carry out fiscal and also socialregulatory functions. Charitable profitable taxes, or so-called solidarity taxes, are of particular scientific and humane interest. These taxes are not sufficiently studied by representatives of the domestic science. Purpose. Our globalist characterize the forms of charitable (solidarity)income taxes. We must to be acquainted with the experience of the leading foreign scientists for regarding the features and purpose of the functioning of the indicated taxes. Methods. The article uses the methods of comparative studies, historical, formalization, analysis and synthesis. Results. The article deals with modern and historical forms of charitable (social) taxes. Charitable taxes can exist in the form of solidarity surcharges to taxes on income or profit, supplements to the price of certain categories of goods, independent taxes on property, wealth, and windfall tax. The experience of leading foreign states (Germany, USA, Great Britain, France) regarding functioning and modifications of solidarity taxes is considered. It was described specific fiscal technology of great interest-the so-called tax shield. Conclusion. The social and political goal of a solidarity tax is to fight against poverty. Solidarity taxes act as a mean to reduce poverty. In general, solidarity taxes increase the progressive nature and redistributive potential of the taxation system. In substance solidarity taxes are intended to finance by government very important from a social point of view, but commercially unprofitable programs and projects. Solidarity taxes are collected in the form of a surcharge to the standard taxes on income of individuals and on profit of firms and companies. Solidarity taxes are included the elements of welfare, of social solidarity and of social justice. These are the benefits of these particular taxes.
Keywords: благодійний податок; податки солідарності; надбавка солідарності; податковий щит; податок на багатство; податок на мільйонерів; податок на непередбачуваний прибуток; charitable taxes; solidarity taxes; solidarity surcharge; tax shield; wealth tax; millionaire's tax; windfall tax